outh Polar chart / from various authorities with amendments and additions to 1939 (Great Britain. Hydrographic Office, 1948)
New editions . Jany. 1942. Small corrections . 1948. Relief shown by spot heights and hachures. Depths shown by soundings.; "Engraved 1926."; "Crown copyright reserved."; "239.48" -- upper right margin.; "Zc 1942" -- lower right margin. Color;